2019
DOI: 10.3390/ijms20184447
|View full text |Cite
|
Sign up to set email alerts
|

IDE Degrades Nociceptin/Orphanin FQ through an Insulin Regulated Mechanism

Abstract: Insulin-degrading enzyme (IDE) was applied to catalyze hydrolysis of Nociceptin/Orphanin 1-16 (OFQ/N) to show the involvement of the enzyme in degradation of neuropeptides engaged in pain transmission. Moreover, IDE degradative action towards insulin (Ins) was inhibited by the OFQ/N fragments, suggesting a possible regulatory mechanism in the central nervous system. It has been found that OFQ/N and Ins affect each other degradation by IDE, although in a different manner. Indeed, while the digestion of OFQ/N is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…It was also shown that insulin-degrading enzyme is applied to catalyze hydrolysis of Nociceptin/ Orphanin 1-16 (OFQ/N) indicating the involvement of the enzyme in the degradation of neuropeptides engaged in pain transmission (Zingale et al 2019). Moreover, IDE degradative action towards insulin was inhibited by the OFQ/N fragments, suggesting a possible regulatory mechanism in the central nervous system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that insulin-degrading enzyme is applied to catalyze hydrolysis of Nociceptin/ Orphanin 1-16 (OFQ/N) indicating the involvement of the enzyme in the degradation of neuropeptides engaged in pain transmission (Zingale et al 2019). Moreover, IDE degradative action towards insulin was inhibited by the OFQ/N fragments, suggesting a possible regulatory mechanism in the central nervous system.…”
mentioning
confidence: 99%
“…IDE cleaves neuropeptides and their released fragments act as inhibitors of IDE activity toward insulin. It is possible that IDE enzyme indirectly participates in neural communication of pain signals and that neuropeptides involved in pain transmission may contribute to the regulation of IDE activity (Zingale et al 2019).…”
mentioning
confidence: 99%
“…Finally, we have also demonstrated that NPAF, but not NPFF, plays an activatory role on the degradation of insulin by IDE in a site-specific manner, favouring the action of the enzyme mainly at the B13-14 insulin cleavage site. Once again, this result demonstrates the pivotal role of IDE in the interplay between NPs and insulin metabolism, giving a molecular insight into the link between type 2 or type 1 diabetes and pain transmission and pain threshold 13,29 .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 64%
“…Once the degradation of the two peptides by IDE was assessed, the next question that needed a more thorough explanation was how this enzymatic activity affects/is affected by insulin degradation. The latter has been already well characterised in our previous reports 13,14,20 and here we investigated only how the presence of insulin in the incubation mixture affects NPFF and NPAF degradation, and how NPFF and NPAF and their fragments affect insulin degradation by IDE. In order to elucidate the first point, that is how insulin affects NPFF and NPAF degradation, we co-incubated insulin, IDE and NPFF or NPAF together and studied the time courses of the cryptic peptides which are formed.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation